Primary and Comprehensive Stroke Centers: History, Value and Certification Criteria - Philip B. Gorelick (Journal of Stroke, 2013)
In the United States (US) stroke care has undergone a remarkable transformation in the past decades at several levels. At the clinical level, randomized trials have paved the way for many new stroke preventives, and recently, several new mechanical clot retrieval devices for acute stroke treatment have been cleared for use in practice by the US Federal Drug Administration. Furthermore, in the mid 1990s we witnessed regulatory approval of intravenous recombinant tissue plasminogen activator for administration in acute ischemic stroke. In the domain of organization of medical care and delivery of health services, stroke has transitioned from a disease dominated by neurologic consultation services only to one managed by vascular neurologists in geographical stroke units, stroke teams and care pathways, primary stroke center certification according to The Joint Commission, and most recently comprehensive stroke center designation under the aegis of The Joint Commission. Many organizations in the US have been involved to enhance stroke care. To name a few, the American Heart Association/American Stroke Association, Brain Attack Coalition, and National Stroke Association have been on the forefront of this movement. Additionally, governmental initiatives by the US Centers for Disease Control and Prevention and legislative initiatives such as the Paul Coverdell National Acute Stroke Registry program have paved the way to focus on stroke prevention, acute treatment and quality improvement. In this invited review, we discuss a brief history of organized stroke care in the United States, evidence to support the value of primary and comprehensive stroke centers, and the certification criteria and process to become a primary or comprehensive stroke center.